Liquidity risk management and supervision : a guide to better practice - Bonner, Clemens; Hilbers, Paul; Lelyveld, Iman Van (London : Incisive Media, 2015)
This book is a practitioner's guide to setting up liquidity risk assessment processes. Expert chapters provide a searching examination of risk practice within the industry.
Includes bibliographical references and index
osc 08/01/2019, ijb, 29/01/2019
Loans
Keywords: Asset-liability management; Bank liquidity; Bank management; Banks and banking--State supervision; Banks and banking -- Risk management